COMMUNITY ECOLOGY OF PARASITES OF SPOTTED BUTTERFISH STROMATEUS STELLATUS (CUVIER, 1829) (PERCIFORMES: STROMATEIDAE) OF COAST ZONE OF CHORRILLOS, LIMA, PERÚ - Iannacone Oliver, José Alberto (2010)
Spotted Butterfish Stromateus stellatus (Cuvier, 1829) is a pelagic species that lives on the continental shelf where it forms small schools. Its geographic distribution includes mainly Ecuador, Peru and Chile, and further south in South America. Eighty specimens of S. stellatus were obtained from the coastal zone of Chorrillos, Lima, Peru between December, 2008 and September, 2009 to assess the community ecology of parasitic fauna. Of the tested fish, 51 were females and 29 were males. The fish showed a mean total length of 16.5 ± 1.8 cm (12 cm to 22.5 cm). Metazoan parasites were collected and plotted using standard parasitological procedures. The parasite assemblage presented a higher percentage of internal parasites (97.2%) compared to ectoparasites. The mean parasite species richness was 0.4 ± 0.6 (0.0 to 3.0). Fifty-four hosts (67.5%) were infected and 26 hosts (32.5%) were infected with at least one parasite species. Three parasite species were found (prevalence and abundance mean values in parentheses): (1) an isopod ectoparasite, Ceratothoa gaudichaudi (H. Milne Edwards, 1840), on the ventral interopercula base (6.25% and 0.06), (2) an endoparasitic digenean, Lecithocladium cristatum Gibson, 1976 in the intestine, (28.75% and 2.08) and (3) a larval nematode endoparasite Hysterothylacium sp. in the intestine (6.25% and 0.11). The importance parasite index showed that L. cristatum had the highest value. No relationship was found between sex and the prevalence or abundance of parasitism by L. cristatum. Total host length was not related the prevalence and mean abundance of infection of L. cristatum. Seasonal variations were found between richness of species, total abundance and prevalence of L. cristatum. No differences in total host length between fish parasitized and unparasitized with L. cristatum were seen. Instead, differences in total lengths between fish parasitized by Hysterothylacium sp. and not parasitized by this worm were observed.